PERAN MEDIASI SUASANA KERJA TERHADAP KEPUASAN KERJA PADA PERUMDA XXX - RAKKAN JAUZAH AKROM; SURAHMAN PUJIANTO (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study aims to test and determine work atmosphere mediates the influence of supervisor cooperation and career growth on job satisfaction at Perusahaan Umum Daerah Air Minum XXX. This study employs a quantitative and causal research method. The sampling technique used is purposive sampling, with the sample consisting of employees of Perusahaan Umum Daerah XXX who have worked for a minimum of five years. Data was collected through the distribution of questionnaires using a Likert scale. A total of 87 employees were sampled. The data were analyzed using SmartPLS version 4.0. Based on the results of hypothesis testing in this study, it is shown that supervisor cooperation has an influence on the work atmosphere, but its effect on job satisfaction is weak. Career growth has an influence on both the work atmosphere and job satisfaction. Work atmosphere has an influence on job satisfaction and is also able to mediate the relationship between supervisor cooperation and career growth with job satisfaction.